ANALISIS PENGARUH PRODUK WISATA, PERSEPSI HARGA DAN PROMOSI TERHADAP KEPUTUSAN WISATAWAN DALAM MENGUNJUNGI OBJEK WISATA (Studi pada Objek Wisata Puri Maerokoco Kota Semarang) - Surgawi, Ilham Surgawi; Sutopo, Sutopo (Faculty of Economics and Business Diponegoro University, 2016)
This research aims to test how much the effect of tourism product, price perception and promotion of tourist decision to visiting tourist attraction on Puri Maerokoco. This research is motivated by a decrease in the number of tourists who visited Puri Maerokoco. The populations used in this research was a tourists attraction Puri Maerokoco. The collection of data by using a questionnaires with a number of samples 100 respondents who visited Puri Maerokoco. This research method, using the technique of non-probability sampling with purposive sampling method. Data obtained from questionnaires, then processed and analyzed using multiple linear regression analysis through the SPSS 22 software. The result of this research shows that all independent variables are the tourism product, price perception and promotion has a positive effect on the dependent variable that is the decision to visit by using t test. Then through f test shows that the three independent variables are proper to examine the dependent variable. Adjusted R Square of 0,393 shows that the independent variables can explain 39,3% the dependent variable that is decision to visit, while the remaining 60,7% is explained by other variables outside of variable that used in this research.